The Role Of The Physical And Sports Teachers In Promoting Healthy Behavior Among Secondary School Pupils In The Light Of Health Perceptions -a Field Study In The Eastern Province Of Algiers, Centre - Latreche , Aissam (sports creativity, 2025)
The research aims to identify the level of health perceptions among teachers of physical education and sports and its role in promoting the healthy behaviour of secondary school pupils. In order to achieve the objectives of the study, the descriptive approach was used in addition to a health perception scale of healthy nutrition, sports health, and healthy habits and behaviours that was administered to a random sample of 40 teachers of physical education and sports from secondary schools distributed in the eastern province in the centre of Algiers during the academic year 2020/2021.The results obtained through the use of appropriate statistical methods show that the level of health perceptions among teachers of physical education and sports is low and that their role in promoting the healthy behaviour of secondary school pupils is not activated. The paper concludes with a set of recommendations aiming to raise the health perceptions of teachers.